Pressing Questions for the Philosophical Life in a Time of Crisis - Matthew Sharpe (University of Warsaw, 2021)
Preview: 2020, the year the coronavirus pandemic spread globally, marked the twenty-fifth year since the publication of Pierre Hadot’s work Philosophy as a Way of Life (translated by co-author Michael Chase). In that time, what began as the research specialization of just a few scholars has become a growing area of philosophical and metaphilosophical inquiry, bringing together researchers from around the globe. Hadot’s key ideas of spiritual exercises, and the very idea of PWL, have been applied to a host of individual thinkers from across the history of philosophy: from the Hellenistic and Roman-era philosophers of direct concern to Hadot, through renaissance thinkers like Petrarch, Lipsius, Montaigne, Descartes, or Bacon, into nineteenth-century thinkers led by Schopenhauer, Kierkegaard, and Nietzsche.In more recent years, more global reflections on the “very idea” of PWL have begun to emerge, as well as dedicated journal editions. In these more recent PWL studies, some of the manifold research questions have begun to be explored, which were opened up by the studies of Pierre and Ilsetraut Hadot, as well as its reception in Michel Foucault’s later work. What implications, after all, does understanding the history of PWL, and the predominance of this metaphilosophical conception in the history of Western thought, have for how we understand the practice(s) of philosophy today? Does recovering the alternative understandings of philosophy as a practice in history necessarily lead to a criticism of contemporary, solely academic or theoretical modes of philosophizing, or is the idea of PWL one which has only historiographical force?